2012
DOI: 10.1007/s10194-012-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide for the prophylaxis of migraine in CADASIL: a preliminary experience

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited microangiopathy caused by NOTCH3 mutations. It is characterized by migraine, with or without aura, ischemic events, psychiatric and cognitive disturbances. There is no approved treatment for migraine prophylaxis in CADASIL, but acetazolamide has been anecdotally reported to be effective. We retrospectively reviewed our database of patients with a genetic diagnosis of CADASIL to identify how many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…[ 5 8 ] Furthermore, little is known about how it responds to therapy and whether the management of migraine in CADASIL should differ from that of migraine in the general population. [ 9 12 ] Epidemiological studies have demonstrated that migraine, in particular migraine with aura, is an independent risk factor for stroke in the general population. [ 13 16 ] However, whether the presence of migraine with aura in CADASIL is predictive of an earlier onset of stroke and a more severe phenotype is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 8 ] Furthermore, little is known about how it responds to therapy and whether the management of migraine in CADASIL should differ from that of migraine in the general population. [ 9 12 ] Epidemiological studies have demonstrated that migraine, in particular migraine with aura, is an independent risk factor for stroke in the general population. [ 13 16 ] However, whether the presence of migraine with aura in CADASIL is predictive of an earlier onset of stroke and a more severe phenotype is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For migraine with aura, conventional prophylactic medications are recommended if attack frequency warrants treatment. Acetazolamide has been anecdotally reported to be effective in the prophylaxis of migraine in CADASIL, but randomized, controlled trials are lacking 57‐59. Acetazolamide has also been suggested to improve overall cerebral hemodynamics in CADASIL, perhaps suggesting a protective effect, but this has also not been proven in controlled trials .…”
Section: Discussion Of Cerebral Autosomal Dominant Arteriopathy With mentioning
confidence: 99%
“…Acetazolamide has been anecdotally reported to be effective in the prophylaxis of migraine in CADASIL, but randomized, controlled trials are lacking. [57][58][59] Acetazolamide has also been suggested to improve overall cerebral hemodynamics in CADASIL, perhaps suggesting a protective effect, but this has also not been proven in controlled trials. 60,61 For acute treatment of migraine attacks, triptans and ergot derivatives should generally be avoided due to the high risk of stroke in these patients, and simple analgesics and non-steroidal anti-inflammatory drugs are preferred.…”
Section: Discussion Of Cerebral Autosomal Dominant Arteriopathy With mentioning
confidence: 99%
“…Prophylactic migraine strategies include good lifestyle and drugs normally used for migraine patients, with caution for amitriptyline, beta-blockers, flunarizine, and topiramate since they may worsen mood and cognitive symptoms (Finocchi et al, 2010). One study demonstrated a beneficial effect of acetazolamide on migraine (Donnini et al, 2012). CADASIL patients with migraine seem to have higher blood homocysteine levels, and B vitamin supplementation lowering homocysteine was seen to decrease migraine severity and frequency (Bousser and Tournier-Lasserve, 2001).…”
Section: Current Therapy and Preventionmentioning
confidence: 99%